A review on slow earthquakes in the Japan Trench - Nishikawa, Tomoaki; Ide, Satoshi; Nishimura, Takuya (Progress in earth and planetary science, 2023)
Slow earthquakes are episodic slow fault slips. They form a fundamental component of interplate deformation processes, along with fast, regular earthquakes. Recent seismological and geodetic observations have revealed detailed slow earthquake activity along the Japan Trench—the subduction zone where the March 11, 2011, moment magnitude ( M w ) 9.0 Tohoku-Oki earthquake occurred. In this paper, we review observational, experimental, and simulation studies on slow earthquakes along the Japan Trench and their research history. By compiling the observations of slow earthquakes (e.g., tectonic tremors, very-low-frequency earthquakes, and slow slip events) and related fault slip phenomena (e.g., small repeating earthquakes, earthquake swarms, and foreshocks of large interplate earthquakes), we present an integrated slow earthquake distribution along the Japan Trench. Slow and megathrust earthquakes are spatially complementary in distribution, and slow earthquakes sometimes trigger fast earthquakes in their vicinities. An approximately 200-km-long along-strike gap of seismic slow earthquakes (i.e., tectonic tremors and very-low-frequency earthquakes) corresponds with the huge interplate locked zone of the central Japan Trench. The M w 9.0 Tohoku-Oki earthquake ruptured this locked zone, but the rupture terminated without propagating deep into the slow-earthquake-genic regions in the northern and southern Japan Trench. Slow earthquakes are involved in both the rupture initiation and termination processes of megathrust earthquakes in the Japan Trench. We then compared the integrated slow earthquake distribution with the crustal structure of the Japan Trench (e.g., interplate sedimentary units, subducting seamounts, petit-spot volcanoes, horst and graben structures, residual gravity, seismic velocity structure, and plate boundary reflection intensity) and described the geological environment of the slow-earthquake-genic regions (e.g., water sources, pressure–temperature conditions, and metamorphism). The integrated slow earthquake distribution enabled us to comprehensively discuss the role of slow earthquakes in the occurrence process of the Tohoku-Oki earthquake. The correspondences of the slow earthquake distribution with the crustal structure and geological environment provide insights into the slow-earthquake-genesis in the Japan Trench and imply that highly overpressured fluids are key to understanding the complex slow earthquake distribution. Furthermore, we propose that detailed monitoring of slow earthquake activity can improve the forecasts of interplate seismicity along the Japan Trench.